Wondering Awe as a Perceptive Aspect of Spirituality and Its Relation to Indicators of Wellbeing: Frequency of Perception and Underlying Triggers - Büssing, Arndt (Frontiers in Psychology, 2021)
Background: Spirituality is a multidimensional construct which includes religious, existentialistic and relational issues, and has different layers such as faith as the core, related attitudes and conviction, and subsequent behaviors and practices. The perceptive aspects of spirituality such as wondering awe are of relevance for both, religious and non-religious persons. These perceptions were related to perceiving the Sacred in life, mindful awareness of nature, others and self, to compassion, meaning in life, and emotional wellbeing. As awe perceptions are foremost a matter of state, it was the aim 1) to empirically analyze the frequency of wondering awe perceptions (i.e., with respect to gender, age cohorts, religious or non-religious persons), and 2) to qualitatively analyze a range of triggers of awe perceptions. Methods: Data from 7,928 participants were analyzed with respect to the frequency of Awe/Gratitude perceptions (GrAw-7 scale), while for the second part of the study responses of a heterogeneous group of 82 persons what caused them to perceive moments of wondering awe were analyzed with qualitative content analysis techniques. Results: Persons who experience Awe/Gratitude to a low extend were the youngest, had lowest wellbeing, and lowest meditation/praying engagement, while those with high GrAw-7 scores were the oldest, had the highest wellbeing, and were more often meditating or praying (p<0.001). Gender had a significant effect on these perceptions, too (Cohen´s d = 0.32). In the qualitative part, the triggers can be attributed to four main categories, Nature, Persons, Unique Moments, and Aesthetics, Beauty and Devotion. Some of these triggers and related perceptions might be more a matter of admiration than wondering awe, while other perceptions could have more profound effects and may thus result in changes of a person´s attitudes and behaviors. Conclusions: Emotionally touching experiences of wondering awe may result in feelings of interconnectedness, prosocial behavior, mindful awareness, and contribute to a persons´ meaning in life and wellbeing, and can also be a health relevant resource. These perceptions can be seen as a perceptive aspect of spirituality, which is not exclusively experienced by religious people but also by non-religious persons.